Profit management from a legal and accounting perspective - Maya Macia Sari; Sakdiah Sakdiah; Novania Trifana; Julia Nuraisyah; Dwi Kumala Sari (Universitas Pendidikan Nasional, 2023)
This study aimed to understand and analyze Profit Management from legal and accounting perspectives. To obtain data related to these variables, researchers made indirect observations. The data used in this study were secondary data, collected through intermediary sources (obtained and recorded by other parties). Secondary data typically included evidence, records, or historical reports compiled in published and unpublished archives (documentary data). The research employed action research, with data collection conducted primarily through intermediary media. Based on the results of this study, the effectiveness of law and accounting was shown to have had a positive and significant impact on profit management within a company. In the case study of banking services, where conventional bank interest was considered usury, financial institutions were required to adhere to Sharia foundations. The values of Sharia law served as a fundamental framework in the societal and national life systems, with Islamic law governing as a rule of life. The pillars and legal conditions of contracts in Sharia were akin to the legal conditions in principle.